Negative Predictors of Heart Rate Variability and Quality of Life in Patients with Heart Failure and Mid-Range Ejection Fraction:A Cross-Sectional and Descriptive Study - Rani Jose Kochupurayil; Neetha Kamath; Ashraf Safia Manzil; Fatima D’Silva; Basavaraj Utagi (Social Medicine)
Introduction. Heart Rate Variability (HRV) is a health indicator and a predictor for sudden cardiac death among patients with Heart Failure with mid-range Ejection fraction (HFmrEF). Many factors have a negative influence on HRV. This study aims to assess the prevalence of known factors associated with low HRV and the correlation between HRV and Quality of life (QoL)among HFmrEF patients. Methods.A cross-sectional descriptive study took place at a tertiary cardiac care center in Kannur district, Kerala, from February to June 2023. The study involved 250 participants with HFmrEF. The researchers collected data using a consecutive sampling technique. They utilized the Minnesota Living with Heart Failure Questionnaire to assess quality of life, and a checklist to identify negative predictors of HRV. They used an HRV finger sensor to assess HRV and performed the analysis using Spearman’s rank correlation coefficient and descriptive statistics. Results.The significant study findings show the prevalence of known negative predictors among HFmrEF patients such as stress (83.6%), male gender (78.8%), poor sleep habits (58.4%), unhealthy eating behavior (55.6%), physical inactivity (53.2%), being overweight (40.8%), age over 60 years(39.2%), smoking (36.8%), diabetes (33.6%), alcoholism (23.6%), and chronic noise exposure (20.4%).The quality of life for patients with HFmrEF was reported as poor in 59% of cases, moderate in 27%, and good in 14%. A moderate negative correlation was identified between the quality of life and HRV score (r = -0.43, p < 0.001).Conclusion. The moderate inverse relationship between HRV and QoL score emphasizes the importance of improving HRV in patients with HF.Stress emerged as the primary adverse predictor, and acknowledging these negative factors can shed light on their management, ultimately contributing to a more favorable prognosis.